Regionalplanung und Golfsport: Ein Beitrag zur Problematik der Deregulierung am Beispiel Münchens - Schemel, Hans-Joachim (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
At present the question whether the construction of golf courses is defensible in spatial planning terms is predominantly evaluated according to suitability criteria of micro-locations, particularly from an ecological point of view, and less according to the suitability of macro-locations extending beyond municipal boundaries. Using the example of the regional plan for Munich, which is currently in the process of revision and updating, the article demonstrates that the argument of deregulation puts the previously clear statements on the admissibility of golf courses into question. The contribution develops regional planning criteria for the evaluation of potential golf course locations with reference to the broader regional context. In this respect the compatibility of golf courses with the character of the landscape and the recreational interests of the public is discussed, and criteria are suggested according to which certain macro-locations should be classified as being unsuitable for golf.